Integrated models of livestock systems for climate change studies. 1. Grazing systems. - Parsons, David J.; Armstrong, A. C.; Turnpenny, J. R.; Matthews, A. M.; Cooper, K. C.; Clark, J. A. (Blackwell Publishing Ltd, 2001)
The potential impact of climate change by the year 2050 on British grazing livestock systems is assessed through the use of simulation models of farming systems. The submodels, consisting of grass production, livestock feeding, livestock thermal balance, the thermal balance of naturally ventilated buildings and a stochastic weather generator, are described. These are integrated to form system models for sheep, beef calves and dairy cows. They are applied to scenarios representing eastern (dry) lowlands, western (wet) lowlands and uplands. The results show that such systems should be able to adapt to the expected climatic changes. There is likely to be a small increase in grass production, possibly allowing an increase in total productivity in some cases.